My Fairy God Somebody - Allen, Charlene Y. (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2024)
"The way Clae's mom tells it, her dad took off when Clae was a baby, end of story. Ever since, it's just been the two of them, living in the coastal city of Gloucester, where Clae is one of the only few Black girls. But when Clae discovers clues about a mysterious person she calls her fairy god somebody, she's determined to know more. Her chance comes when she's accepted into a summer journalism program in New York City, where her parents lived before she was born. With a couple of leads and a steel resolve, Clae leaves home for the first time to find out about her history. New York is as full of magic as it is mystery, not to mention romance. From Brooklyn to Broadway, Clae and her new friends, Nze and Joelle, explore neighborhood haunts and hustles, discovering a family trail that someone's tried hard to bury. So who is the fairy god somebody? And can Clae use her sleuthing skills to find out the truth?"--Provided by publisher.
new YA book 2024 winter.
Keywords: African American teenage girls -- Fiction; African Americans -- Fiction; Teenage girls -- Fiction; Families -- Fiction; Parents -- Fiction; Friendship -- Fiction; Identity (Psychology); Coming of age; Female friendship; Bildungsromans; Friendship in adolescence; Journalism; Absentee fathers; New York (N.Y.) -- Fiction; Young adult fiction